the students of the bullying action in high school country 5 pekanbaru - rekha nurvadila, rekha nurvadila (Afiasi : Jurnal Kesehatan Masyarakat, 2020)
Bullying continues to increase from year to year, one of among Indonesian students. Among students, the high school level is the level most encountered by bullying according to several studies. The objective of this research is to find out students' perceptions of their bullying in school. The research method used is a qualitative design with phenomenological study and purposive sampling as data collection techniques. This study involved 10 participants who were male. The data analysis used the Collaizi method, which then gets four themes, including the definition of bullying in generally like a hardness, torturing and the wickedness. The bullying classification carried out by the bully like verbal bullying, physical bullying and psychological bullying. Student’s perceptions of bullying with consider as a gratified and usually conducted, and than feelings of students after bullying like feel contrition and feel their action not naturally. The results of this research can be expected to be a directive study, specially for school side, in order to decrease bullying action in school surroundings with give materials related bullying action. The students also must be knowing endangered of bullying action who their doing in order to awareness to doing continuous. Bibliography: 19 (2008-2017) Keywords: Bullying, Bully, Student, Perception.